FORMATION OF HIERARCHICAL CUO NANOWIRES ON A COPPER SURFACE VIA A ROOM-TEMPERATURE SOLUTION-IMMERSION PROCESS - FUENTES,S (Sociedad Chilena de Química, 2010)
CuO nanowires were successfully made through a simple wet chemical method at room temperature by immersing on copper sheets in a 4 M ammonia solution for 4 days and then subjecting it to heat treatment. Immersion time and heat treatment have an important effect on the length, diameter, and density of the CuO nanostructures. X-ray powder diffraction (XRD) patterns indicated that the samples are composed of a single phase, CuO. Scanning electron microscopy (SEM), transmission electron microscopy (TEM), and Raman spectroscopy studies showed that the wet-treated samples consisted of nanofiber-like structures of monoclinic CuO, while the heat-treated samples consisted of well-defined nanowires which also exhibited the monoclinic phase.